Respuesta :

Step-by-step explanation:

1.7m + 2(m + 1) = 9m + 5

Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation :

7*m+2*(m+1)-(9*m+5)=0

(7m +  2 • (m + 1)) -  (9m + 5)  = 0

-3  = 0

Solve :    -3   =  0

This equation has no solution.

A a non-zero constant never equals zero.

2.4m+2(m+1)=9m+5

m=−1

Pull out like factors :

-3m - 3  =   -3 • (m + 1)

-3 • (m + 1)  = 0

Solve :    -3   =  0

This equation has no solution.

A a non-zero constant never equals zero.

Solve  :    m+1 = 0

Subtract  1  from both sides of the equation :

                     m = -1

7m+2m+2=9m+5

9m+2=9m+5
-2 -2
9m=9m+3
-9m -9m
0m=3